Molecular Cloning, Characterization, and mRNA Expression of Hemocyanin Subunit in Oriental River Prawn Macrobrachium nipponense - Youqin Kong; Liqiao Chen; Zhili Ding; Jianguang Qin; Shengming Sun; Ligai Wang; Jinyun Ye (International Journal of Genomics)
Hemocyanin is a copper-containing protein with immune function against disease. In this study, a hemocyanin subunit named MnHc-1 was cloned from Macrobrachium nipponense. The full-length cDNA of MnHc-1 was 2,163 bp with a 2,028-bp open reading frame (ORF) encoding a polypeptide of 675 amino acids. The MnHc-1 mRNA was expressed in the hepatopancreas, gill, hemocytes, intestine, ovary, and stomach, with the highest level in the hepatopancreas. In the infection trial, the MnHc-1 mRNA transcripts in the hemocytes were significantly downregulated at 3 h after injection of Aeromonas hydrophila and then upregulated at 6 h and 12 h, followed by a gradual recovery from 24 to 48 h. The MnHc-1 transcriptional expression in the hepatopancreas was measured after M. nipponense were fed seven diets with 2.8, 12.2, 20.9, 29.8, 43.1, 78.9, and 157.1 mg Cu kg−1 for 8 weeks, respectively. The level of MnHc-1 mRNA was significantly higher in the prawns fed 43.1–157.1 mg Cu kg−1 diet than in that fed 2.8–29.8 mg Cu kg−1 diet. This study indicated that the MnHc-1 expression can be affected by dietary copper and the hemocyanin may potentially participate in the antibacterial defense of M. nipponense.